Desempenho individual e em comunidades de plantas de soja formadas por diferentes proporções de sementes de alto e baixo vigor na linha de cultivo - Pino, Mateus (2013)
The objective of this study was to evaluate the influence of low and high vigor of soybean seeds on agronomic characteristics , yield components and seed yield, in individually plants and on the communities of plants generated by different proportions of plants originated from high and low vigor seeds on the crop row. The experiment was conducted in the county of Selbach - RS, in a no-till seeding system over ryegrass straw, in 2012/2013 crop year. Was used the cultivar of soybean FPS Urano RR, of short-cycle. The experiment design was completely randomized, with five replications. Were selected seven different proportion of high and low vigor seed, along the sowing row. Were evaluated agronomic characteristics, yield components and seed yield on plants and on the communities formed. Based on the results obtained it was found that: plants from high vigor seeds show higher than plants arising from low vigor, in V5 and R8 phenological stages; Based on the results obtained it was found that: plants from high vigor seeds show greater height than plants arising from low vigor, in V5 and R8 phenological stages; even when communities are formed only by plants arising from low vigor seeds, these can not reach yield levels found in plants arising from high vigor seeds; number and weight of seeds per plant, are the yield components that more contributed to increase yield; the plant community formed only of plants grown from seeds of high vigor, shows seed yield per area 29% more, comparatively, to one formed only of plants from low vigor seeds.